High hardness, low viscosity uv curable potting adhesive composition
The problem of inefficiency of existing 2k epoxy adhesives is solved by developing a UV curable adhesive composition containing bifunctional epoxy acrylate oligomers and other functional components, achieving low viscosity Provides high hardness and rapid curing effects, improving productivity and process efficiency of small precision electronic components.
Patent Information
- Application Number
- CN202380047420.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-17
- Filing Date
- 2023-05-19
- Publication Date
- 2025-02-07
AI Technical Summary
Existing 2k epoxy adhesives exhibit high hardness at medium viscosity, but their mixing and high-temperature curing cycles are inefficient and cannot meet the productivity and thermal curing requirements of small precision electronic components.
A UV curable adhesive composition has been developed, which contains 35-45% of bifunctional epoxy acrylate oligomer, bifunctional acrylate monomer, bridged bifunctional acrylate monomer, and adhesion accelerator. , stabilizers, defoamers and photoinitiators can provide high hardness and fast curing at low viscosity.
The composition provides high hardness at low viscosity, fast curing without microcracks and bubbles, improves process productivity and saves energy, and is suitable for potting of small precision electronic components.
Smart Images

Figure BDA0005189949170000051 
Figure BDA0005189949170000061 
Figure BDA0005189949170000062
Abstract
Description
Technical Field
[0001] The present invention relates to a UV curable adhesive composition, which comprises a difunctional epoxy acrylate oligomer, a difunctional acrylate monomer, a bridged difunctional acrylate monomer, an adhesion promoter, a stabilizer, a defoamer and a photoinitiator. The composition according to the present invention has high hardness and low viscosity and is suitable for use in a radio frequency identification transponder. Background Art
[0002] In the rapidly growing electronics market, several sophisticated small / micro components are used, such as RFID transponders, which are used in various applications for identification, tracking, anti-counterfeiting, etc. via chips or antennas.
[0003] RFID transponders and antennas are precision components that must be protected from physical and / or mechanical stress and dust contamination. To avoid such damage, the components are usually covered with a potting adhesive that exhibits high hardness. Currently commercially available 2k epoxy adhesives exhibit high hardness characteristics at medium viscosity. However, 2k epoxy adhesives require a large number of mixing and high-temperature curing cycles, which ultimately affects process productivity and therefore cannot meet existing market demand.
[0004] To overcome the disadvantages of 2k epoxy adhesives, one-component UV curable adhesives are preferred as they can offer many advantages such as cure speed, cure on demand, ease of handling and their ability to bond to different substrates.
[0005] UV curable adhesives, which typically contain urethanes, epoxies, and acrylates, provide key properties through free radical polymerization. Reactive diluents (e.g., monofunctional and difunctional acrylate monomers) are not only easy to reduce viscosity, but also easy to fine-tune adhesive properties according to application needs. Photoinitiators promote photo-free radical polymerization in the presence of UV light based on their absorption wavelength in nanometers (nm). UV curable adhesives also contain various performance adhesives, defoamers, and stabilizers for better handling and shelf life stability.
[0006] Therefore, there is a need for an adhesive that provides good productivity, is capable of potting at high viscosities, and meets the mixing and thermal curing requirements of small precision electronic components. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figures 1a and 1b Examples illustrate a potted RFID and zinc housing and a potted RFID and zinc housing attached to an electric toothbrush.
[0008] Figures 2a and 2bEncapsulated and bonded RFIDs prepared from the composition according to Example 2 are illustrated.
[0009] 3a and 3b illustrate the deformation before bonding, and FIG. 3c illustrates the deformation after bonding.
[0010] Figure 4 The example illustrates micro-cracks in a potted RFID. Summary of the invention
[0011] The present invention relates to a UV curable adhesive composition comprising: a) 35 to 45 wt % of a difunctional epoxy acrylate oligomer, based on the total weight of the composition; b) a difunctional acrylate monomer; c) 2 to 7 wt % of a bridged difunctional acrylate monomer, based on the total weight of the composition; d) an adhesion promoter; e) a stabilizer; f) a defoamer; and g) a photoinitiator.
[0012] The present invention also relates to a cured product comprising the UV-curable adhesive composition according to the present invention.
[0013] The present invention comprises the use of a UV curable adhesive composition or a cured product according to the present invention in a radio frequency identification transponder. DETAILED DESCRIPTION
[0014] In the following paragraphs, the present invention will be described in more detail. Unless there is a clear contrary indication, each aspect described in this way can be combined with any one or more other aspects. In particular, any feature indicated as preferred or advantageous can be combined with any one or more other features indicated as preferred or advantageous.
[0015] In the context of the present invention, unless the context requires otherwise, the terms used are to be interpreted according to the following definitions.
[0016] As used herein, the singular forms "a," "an," "said," and "the" include singular and plural referents unless the context clearly dictates otherwise.
[0017] As used herein, the terms "comprising" and "containing" are synonymous with "including" or "comprising", are inclusive or open-ended, and do not exclude additional, unrecited members, elements, or method steps.
[0018] As used herein, the term "consisting of" excludes any elements, ingredients, members, or method steps not specified.
[0019] "Preferred", "preferably", "desirably" and "particularly" are often used herein to refer to embodiments of the present disclosure that may provide specific benefits in certain circumstances. However, the listing of one or more preferred, preferred, desired or particular embodiments does not mean that other embodiments are not useful, and is not intended to exclude those other embodiments from the scope of the present disclosure.
[0020] As used throughout this application, the words "may" or "may" are used in a permissive sense (ie, meaning having the potential to), rather than in a mandatory sense.
[0021] Recitations of numerical endpoints include all numbers and fractions within the corresponding range, as well as the recited endpoints.
[0022] Unless otherwise specified, all percentages, parts, ratios, etc. mentioned herein are based on weight.
[0023] When an amount, concentration or other value or parameter is expressed in the form of a range, a preferred range or a preferred upper value and a preferred lower value, it should be understood that any range obtained by combining any upper limit or preferred upper value with any lower limit or preferred lower value is specifically disclosed, regardless of whether the obtained range is explicitly mentioned in the context.
[0024] As used herein, the term "one-component (1K) composition" refers to a composition in which the components of the composition are mixed together during storage of the composition, but the properties of the composition (including viscosity) remain sufficiently consistent during the storage time to allow successful subsequent use of the composition.
[0025] A "two-component (2K) composition" is understood to be a composition in which the first component / part and the second component / part have to be stored in separate containers due to their (high) reactivity. The two components / parts are mixed only shortly before application and then react, usually without additional activation, forming bonds and thus a polymer network. Here, higher temperatures can be applied to accelerate the crosslinking reaction.
[0026] As used herein, the term "radio frequency identification (RFID)" refers to the material's use of electromagnetic fields to automatically identify and track tags attached to objects. RFID systems consist of tiny radio transponders, radio receivers, and transmitters. When triggered by an electromagnetic interrogation pulse from a nearby RFID reader device, the tag transmits digital data (usually an identifying inventory number) back to the reader.
[0027] The entire contents of all references cited in this specification are incorporated herein by reference.
[0028] Unless otherwise defined, all terms (including technical and scientific terms) used in disclosing the present invention have the meaning commonly understood by one of ordinary skill in the art to which the present invention belongs. By way of further guidance, term definitions are included to better understand the teachings of the present invention.
[0029] The present invention relates to a UV curable adhesive composition comprising: a) 35 to 45 wt % of a difunctional epoxy acrylate oligomer, based on the total weight of the composition; b) a difunctional acrylate monomer; c) 2 to 7 wt % of a bridged difunctional acrylate monomer, based on the total weight of the composition; d) an adhesion promoter; e) a stabilizer; f) a defoamer; and g) a photoinitiator.
[0030] The composition according to the present invention provides high hardness when used for potting 0.5 to 1 mm thick components in a low viscosity solution. The composition can be cured quickly without micro cracks and bubbles while providing good dimensional stability - no bending of components. The composition further provides improved process productivity and energy savings compared to existing 2k epoxy adhesive solutions.
[0031] The UV curable adhesive according to the present invention comprises a difunctional epoxy acrylate oligomer. The difunctional epoxy acrylate oligomer is used because it is a rigid molecule that provides high reactivity, hardness and excellent chemical and abrasion resistance while having very low non-yellowing color after curing.
[0032] Suitable difunctional epoxy acrylate oligomers may be selected from bisphenol A epoxy acrylate, difunctional bisphenol A epoxy acrylate, novolac epoxy acrylate, aromatic epoxy-modified acrylic resin, cresol novolac epoxy acrylate, and mixtures thereof. Preferably, the difunctional epoxy acrylate oligomer is bisphenol A epoxy acrylate.
[0033] The above preferred difunctional bisphenol A epoxy acrylates are all very rigid molecules that provide high reactivity, hardness, and excellent chemical and abrasion resistance while having very low non-yellowing color after curing.
[0034] Commercially available difunctional epoxy acrylate oligomers suitable for use in the present invention include, but are not limited to, epoxy acrylic prepolymer CN104 from Sartomer (Gz) Chemicals Ltd., novolac epoxy acrylate (NAM-R205), epoxy acrylate (NAM3000A) and cresol novolac epoxy acrylate (NAM-R9259) from Nagase America, epoxy acrylate (Laromer 9019) from BASF, and epoxy acrylate (CN110 NS) and epoxy acrylate (CN120 NS) from Sartomer.
[0035] The difunctional epoxy acrylate oligomer is present in the composition at 35 to 45 wt %, preferably 37 to 44 wt %, and more preferably 39 to 43 wt %, based on the total weight of the composition.
[0036] If the amount of the difunctional epoxy acrylate oligomer is higher than 45%, the overall viscosity of the product may increase toward the higher side, which may be difficult to dispense in the potting of small components. An amount less than 35% may result in a viscosity toward the lower side, which may be easy to dispense, however it may spread out of the potting mold and disturb the size of the component.
[0037] The UV curable adhesive according to the present invention contains a difunctional acrylate monomer. The difunctional acrylate monomer acts as a reactive diluent to adjust the viscosity of the composition, and it also provides flexibility and hydrophobicity to the composition.
[0038] Suitable difunctional acrylate monomers may be difunctional aliphatic acrylate monomers, which are preferably selected from hexanediol diacrylate, 1,4-butanediol diacrylate, 1,12-dodecanediol diacrylate, diethylene glycol diacrylate, and mixtures thereof; preferably, the difunctional acrylate monomer is hexanediol diacrylate.
[0039] Aliphatic difunctional acrylate monomers are preferred because they are flexible and transparent in color, whereas aromatic monomers tend to be rigid and promote yellowing of color.
[0040] Commercially available difunctional acrylate monomers suitable for use in the present invention include, but are not limited to, hexanediol diacrylate SR238NS from Sartomer (Gz) Chemicals Ltd.
[0041] The difunctional acrylate monomer may be present in the composition in an amount of 40 to 50 wt %, preferably 42 to 48 wt %, and more preferably 44 to 47 wt %, based on the total weight of the composition.
[0042] The above selected range can provide the composition with a desired viscosity.
[0043] The UV curable adhesive according to the present invention comprises a bridged difunctional acrylate monomer. The bridged difunctional acrylate monomer provides the composition with non-yellowing, good flexibility and high Tg characteristics.
[0044] Preferably, the bridging difunctional acrylate monomer is selected from tricyclodecane dimethanol diacrylate, isobornyl methacrylate, cyclohexanedimethanol diacrylate, and mixtures thereof; preferably, the bridging difunctional acrylate monomer is tricyclodecane dimethanol diacrylate.
[0045] Tricyclodecane dimethanol diacrylate is particularly preferred because it prevents / reduces shrinkage of the component during cure. In addition, it provides non-yellowing color and good flexibility to the composition, as well as high Tg characteristics.
[0046] Commercially available bridged difunctional acrylate monomers suitable for use in the present invention include, but are not limited to, tricyclodecane dimethanol diacrylate SR833NS from Sartomer (Gz) Chemicals Ltd.
[0047] The bridged difunctional acrylate monomer is present in the composition at 2 to 7 weight percent, preferably 2.5 to 6 weight percent, and more preferably 3 to 5 weight percent, based on the total weight of the composition.
[0048] If the amount of the difunctional acrylate monomer is above 7%, the overall viscosity of the product may increase too much, which may make it difficult to dispense in small quantities, and further, it may also negatively affect the desired hardness. An amount less than 2% may not achieve the desired hardness range.
[0049] UV curable adhesive according to the present invention comprises adhesion promoter.Adhesion promoter serves as the interface between organic adhesive material and organic / inorganic substrate, to strengthen the adhesion between two materials.These two materials are usually different, so that it is difficult to form strong adhesive bonding between them, for example they are different in compatibility, chemical reactivity, surface characteristics and thermal expansion coefficient.The effect of adhesion promoter is to bond these different materials into strong cohesive bonding structure chemically and physically.Adhesion promoter can give the resistance to environment and other damage forces (for example heat and moisture), and these forces usually act on bonding site to destroy bond strength.
[0050] Preferably, the adhesion promoter is selected from glycidoxypropyltrimethoxysilane, acrylic acid, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxyethyltrimethoxysilane, γ-glycidoxymethyltrimethoxysilane, γ-glycidoxymethyltriethoxysilane, γ-glycidoxyethyltriethoxysilane, γ-glycidoxypropyltriethoxysilane; and 8-glycidoxy-n-octyltrimethoxysilane, and mixtures thereof; preferably, the bifunctional adhesion promoter is selected from glycidoxypropyltrimethoxysilane, acrylic acid and mixtures thereof.
[0051] Commercially available adhesion promoters suitable for use in the present invention include, but are not limited to, acrylic acid glacial from BASF, and Silquest A 187 from Momentive.
[0052] The adhesion promoter may be present in the composition at 2 to 8 wt%, preferably 3 to 7 wt% and more preferably 3.5 to 5.5 wt% based on the total weight of the composition.
[0053] The above selected range provides ideal adhesion promotion; furthermore, if the amount of adhesion promoter is higher than 8%, it may negatively affect the curing properties.
[0054] The UV curable adhesive according to the present invention contains a stabilizer, which is used to inhibit the formation of peroxy radical intermediates.
[0055] The stabilizer suitable for use in the present invention can be selected from 2-tert-butylhydroquinone, butylhydroxytoluene, 1,4-benzoquinone, anthraquinone, hydroquinone, methoxyphenol-2,6-di-tert-butyl-4-methoxyphenol, 4-tert-butylcatechol, and mixtures thereof; preferably, the stabilizer is selected from 2-tert-butylhydroquinone, butylhydroxytoluene and mixtures thereof.
[0056] Commercially available stabilizers suitable for use in the present invention include, but are not limited to, 2-tert-butylhydroquinone from LOBA Chemie, and butylated hydroxytoluene Topanol OC from Azelis.
[0057] The stabilizer may be present in the composition at 0.01 to 0.1 wt %, preferably 0.02 to 0.09 wt %, and more preferably 0.04 to 0.08 wt %, based on the total weight of the composition.
[0058] The above selected ranges can provide the desired stability to the composition without negatively affecting other properties.
[0059] The UV curable adhesive composition according to the present invention comprises a defoaming agent. During the preparation of the composition according to the present invention, a defoaming agent may be added to the composition during the dispersion process to reduce foaming.
[0060] Defoamers which are also known in the field of detergents and cleaning agents for use in washing machines, dishwashers, etc. and which are available on the market for this purpose can be used. The defoamers can be non-silicone defoamers or defoamers containing silicone. In particular, defoamers containing nonionic surfactants / polymers or silicon compounds with a defoaming effect are suitable as defoamers. For example, the latter can be selected from oligomeric or polymeric siloxanes, polyether siloxanes, aminosiloxanes, alkoxylated siloxanes, siloxane copolymers and their alkoxylation products, siloxanediol polymers and hydrophilically modified silicon compounds.
[0061] Any commercially available defoamer can be used in the composition according to the invention. Defoamers suitable for use in the present invention may, for example, be silicone-free polymer defoamers. Defoamers may be selected from commercially available products, examples of which include, but are not limited to: TEGO Airex 990, TEGO Rad 2300 and TEGO Rad 2100 from Evonik; Wet 270 and Wet 500 from Evonik, and BYK-A505, BYK-A530, BYK-A515 from BYK.
[0062] The defoaming agent may be present in the composition at 0.05 to 0.35 wt %, preferably 0.1 to 0.30 wt %, and more preferably 0.1 to 0.25 wt %, based on the total weight of the composition.
[0063] Applicants have found that these amounts are preferred because amounts above 0.35% may negatively affect coating properties (eg, surface wettability), while amounts below 0.05% may not provide the desired defoaming effect.
[0064] The UV curable adhesive composition according to the present invention comprises a photoinitiator. The photoinitiator functions to initiate photopolymerization of the chemically unsaturated oligomer combined with the mono- or polyfunctional monomer.
[0065] The photoinitiator suitable for use in the present invention can be selected from hydroxyhexylphenol ketone, 1-hydroxycyclohexyl phenyl ketone; benzophenone; 4-chlorobenzophenone; 2-benzoylbenzoic acid methyl ester; phenyl bis (2,4,6-trimethylbenzoyl) phosphine oxide; diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide; 4-phenylbenzophenone; 2-methyl-1-[4-ethylthio)phenyl]-2-(4-morpholinyl)-1-propanone (2-methyl-1-[4-ethylthio)phenyl]-2-(4-morpholinyl)-1-propanone holinyl)-1-propanone); 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; 2,4-diethylthioxanthone; ethyl-4-(dimethylamino)benzoate; -(4'-methylphenylthio)-benzophenone, and mixtures thereof; preferably, the defoaming agent is 1-hydroxyhexylphenol ketone.
[0066] Commercially available photoinitiators suitable for use in the present invention include, but are not limited to, Irgacure 184 from Ciba Speciality Chemicals.
[0067] The photoinitiator may be present in the composition at 1 to 10 wt %, preferably 2 to 8 wt %, and more preferably 3 to 5 wt %, based on the total weight of the composition.
[0068] Applicants have found that these amounts are preferred because amounts above 10% may provide a tacky surface, while amounts below 1% may delay cure.
[0069] The viscosity of the UV curable adhesive composition according to the present invention is preferably 80 to 140 cPs, wherein the viscosity is measured according to the ASTM 4287 test method.
[0070] Applicants have found that the above viscosity range is ideal. Typically, high viscosity adhesives do not work well when used to pot small electronic components (such as RFID), while low viscosity adhesives may flow easily, which may have a negative impact on the size of the component. When the viscosity is too low, the composition may lose its dimensional stability and flatness of the potted component after curing, which may result in poor yields during final assembly and hairline cracks on the edges.
[0071] The refractive index of the UV curable adhesive composition according to the present invention is preferably equal to or lower than 1.56. The refractive index is measured according to ASTM D1218-21.
[0072] Refractive indices equal to or lower than 1.56 are preferred, since values lower than 1.56 provide compositions with visual clarity.
[0073] The halogen content of the UV curable adhesive composition according to the present invention is preferably less than 1500 ppm. The halogen content is measured according to ASTM D4327-03.
[0074] Halogen contents below 1500 ppm are preferred because they enable good potting of electronics. In addition, low halogen content promotes corrosion resistance and electromigration resistance at high temperatures and humidity. Furthermore, low halogen content has advantages other than environmental aspects, such as halogen-free circuit boards having better dielectric breakdown ratings, lower coefficients of thermal expansion (which can provide higher operating temperatures), and lower moisture absorption.
[0075] The present invention also relates to a cured product comprising the UV-curable adhesive composition according to the present invention.
[0076] The cured product according to the present invention has a Shore hardness equal to or higher than 82, wherein the Shore hardness is measured according to ASTM2240.
[0077] In a highly preferred embodiment, the cured product has a Shore hardness of 82 to 84.
[0078] The above hardness range has been found to be ideal because potting adhesives must require high hardness to protect small electronic components (such as RFID transponders) from physical / mechanical stress and contamination.
[0079] According to the present invention, the UV curable adhesive composition and / or the cured product may be used in a radio frequency identification transponder.
[0080] The encapsulated RFID can be used, for example, in electric toothbrushes. Figures 1a and 1b A potted RFID (potting has been done by using the composition according to the invention) and a zinc casing are illustrated in FIG.
[0081] Example
[0082] Test Method
[0083] The Shore D hardness is measured by preparing a sheet with a thickness of 1.5 mm. The sheet is prepared by UVA LOC1000 equipment under a mercury lamp with a curing time of 10 seconds. Four sheets are then stacked one on top of the other to have the total thickness required according to ASTM.
[0084] Viscosity is measured according to the ASTM 4287 test method.
[0085] Examples according to the invention were prepared and tested. Table 1 illustrates these compositions. The viscosity and Shore D hardness of Examples 1 to 2 were measured according to the test methods described above and the results are illustrated in Table 2 below.
[0086] Table 1
[0087]
[0088]
[0089] Table 2
[0090]
[0091] Example 1 was prepared, which contains a combination of epoxy acrylate and a bridged difunctional aliphatic acrylate monomer, wherein the latter provides toughness and additionally serves as a reactive diluent. Example 1 does not cause microcracking and dimensional deformation at low viscosities in potting applications for RFID (this is illustrated in Figure 1).
[0092] Example 2 is an adhesive with added pigments (red and yellow) that appears amber and has a desired refractive index value of 1.50. The halogen content of Example 2 is 1400 ppm, which is within the desired range. In addition, Example 2 shows the same characteristic performance as Example 1 without affecting the desired Shore D hardness and viscosity range.
[0093] Commercially available samples LOCTITE AA3081 and LOCTITE AA3555 were used as reference materials.
[0094] AA 3081 TM It is a 1k UV curable modified acrylate and is a clear liquid when uncured. It is designed for bonding cannulas into sleeves, syringes and lancets. AA 3081 TM Excellent adhesion to glass, metal and certain thermoplastic substrates. The ability of this product to fluoresce under black light aids in the inspection of adhesives in bonded assemblies. The low viscosity of this product makes it ideal for applications where it is necessary to wick the adhesive into pre-assembled parts.
[0095] AA 3555 TM It is a 1k (visible light) curable acrylate urethane and is a clear yellow liquid with a green tint when uncured. AA 3555 TM Cures rapidly when exposed to visible light of sufficient intensity. The fast curing properties make it ideal for potting applications requiring fast and deep cure. AA 3555 TM The ability to fluoresce under black light helps inspect bonded assemblies for the presence of adhesive. AA 3555 TM Suitable for a wide variety of applications requiring bonding of polycarbonate to itself and a variety of other substrates without causing stress cracking at typical molding stress levels.
[0096] The viscosity and Shore D hardness of LOCTITE AA3081 and LOCTITE AA3555 were measured according to the test methods described above, and the results are illustrated in Table 3 below.
[0097] Table 3
[0098]
[0099] The following comparative examples were prepared and tested. Comparative Examples 1 to 6 are illustrated in Table 4 below. The viscosity and Shore D hardness of Comparative Examples 1 to 6 were measured according to the test methods described above, and the results are illustrated in Table 5 below.
[0100] Table 4
[0101]
[0102]
[0103] Note: “CE.” refers to comparative example.
[0104] Table 5
[0105]
[0106] Comparative Examples 1 and 2 comprise urethane acrylate oligomers, mono- and multi-functional acrylate reactive diluents, additives, stabilizers and photoinitiators. Viscosity, appearance and cure speed are within the desired values; however, the Shore D hardness is <80 due to the flexible nature of the backbone of the polymer used. Comparative Examples 3 and 4 comprise trifunctional acrylate monomers and bridged difunctional acrylate monomers, which result in a Shore D hardness >80; however, due to the high crosslinking density of the reactive diluents, microcracks were observed in the RFID element after curing. Comparative Examples 5 and 6 comprise a combination of urethane acrylate and epoxy acrylate oligomers with reactive diluents, which results in a Shore D hardness that is not the desired. Figures 3a and 3b illustrate deformation before bonding, and Figure 3c illustrates deformation after bonding, which is caused by the material being too soft. Figure 4 The example illustrates microcracks in potted RFIDs, which are caused by high cross-link density.
Claims
1. A UV curable adhesive composition comprising a) 35 to 45 wt % of a difunctional epoxy acrylate oligomer, based on the total weight of the composition; b) difunctional acrylate monomer; c) 2 to 7 wt % of a bridged difunctional acrylate monomer, based on the total weight of the composition; d) adhesion promoter; e) stabilizers; f) defoaming agents; and g) Photoinitiator.
2. The UV curable adhesive composition according to claim 1, wherein the difunctional epoxy acrylate oligomer is selected from bisphenol A epoxy acrylate, difunctional bisphenol A epoxy acrylate, novolac epoxy acrylate, aromatic epoxy-modified acrylic resin, cresol novolac epoxy acrylate, and mixtures thereof, preferably the difunctional epoxy acrylate oligomer is bisphenol A epoxy acrylate.
3. The UV curable adhesive composition according to claim 1 or 2, wherein the difunctional acrylate monomer is a difunctional aliphatic acrylate monomer, which is preferably selected from hexanediol diacrylate, 1,4-butanediol diacrylate monomer, 1,12-dodecanediol diacrylate monomer, diethylene glycol diacrylate monomer, and mixtures thereof; preferably, the difunctional acrylate monomer is hexanediol diacrylate.
4. The UV curable adhesive composition according to any one of claims 1 to 3, wherein the bridged bifunctional acrylate monomer is selected from tricyclodecane dimethanol diacrylate, isobornyl methacrylate, cyclohexanedimethanol diacrylate, and mixtures thereof, preferably the bridged bifunctional acrylate monomer is hexanediol diacrylate.
5. A UV curable adhesive composition according to any one of claims 1 to 4, wherein the adhesion promoter is selected from the group consisting of glycidoxypropyltrimethoxysilane, acrylic acid, γ-glycidoxypropyltrimethoxysilane, γ-glycidoxyethyltrimethoxysilane, γ-glycidoxymethyltrimethoxysilane, γ-glycidoxymethyltriethoxysilane, γ-glycidoxyethyltriethoxysilane, γ-glycidoxypropyltriethoxysilane; and 8-glycidoxyoctyltrimethoxysilane, and mixtures thereof; preferably, the bifunctional adhesion promoter is selected from the group consisting of glycidoxypropyltrimethoxysilane, acrylic acid, and mixtures thereof.
6. The UV curable adhesive composition according to any one of claims 1 to 5, wherein the stabilizer is selected from 2-tert-butylhydroquinone, butylhydroxytoluene, 1,4-benzoquinone, anthraquinone, hydroquinone, methoxyphenol-2,6-di-tert-butyl-4-methoxyphenol, 4-tert-butylcatechol, and mixtures thereof; preferably, the stabilizer is selected from 2-tert-butylhydroquinone, butylhydroxytoluene, and mixtures thereof.
7. The UV curable adhesive composition according to any one of claims 1 to 6, wherein the defoamer can be a non-silicone defoamer or a silicone-containing defoamer, preferably selected from oligomeric or polymeric siloxanes, polyether siloxanes, aminosiloxanes, alkoxylated siloxanes, siloxane copolymers and their alkoxylation products, siloxane diol polymers and hydrophilically modified silicon compounds, and mixtures thereof.
8. A UV curable adhesive composition according to any one of claims 1 to 7, wherein the photoinitiator is selected from hydroxyhexylphenol ketone, 1-hydroxycyclohexylphenyl ketone; benzophenone; 4-chlorobenzophenone; methyl 2-benzoylbenzoate; phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide; diphenyl(2,4,6-trimethylbenzoyl)phosphine oxide; 4-phenylbenzophenone; 2-methyl-1-[4-ethylthio)phenyl]-2-(4-morpholinyl)-1-propanone; 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; 2,4-diethylthioxanthone; ethyl-4-(dimethylamino)benzoate; -(4'-methylphenylthio)-benzophenone, and mixtures thereof; preferably the defoaming agent is 1-hydroxyhexylphenol ketone.
9. The UV curable adhesive composition according to any one of claims 1 to 8, wherein the viscosity of the composition is 80 to 140 cPs, wherein the viscosity is measured according to ASTM 4287 test method.
10. A cured product comprising the UV curable adhesive composition according to any one of claims 1 to 9. 11 . The cured product according to claim 11 , wherein the cured product has a Shore hardness equal to or higher than 82, wherein the Shore hardness is measured according to ASTM 2240.
12. Use of the UV curable adhesive composition according to any one of claims 1 to 9 or the cured product according to claim 10 or 11 in a radio frequency identification transponder.